(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the use of the theory of constructivism as a framework for understanding the root causes of border disputes in Central Asia. Constructivism emphasizes the importance of ideas, norms, and values in shaping international relations, and suggests that conflict resolution can be achieved through dialogue and the creation of common norms and values. By applying this approach to the border conflicts in Central Asia, the article suggests that the region’s rich history and cultural diversity should be highlighted as a means of fostering cooperation and finding joint solutions to border problems. The article provides an overview of Central Asia, its history, and the border disputes that have plagued the region since the collapse of the Soviet Union in 1991. It also discusses the challenges posed by the artificial borders created during the Soviet era, which have led to the separation of traditional communities and the emergence of ethnoculturally diverse territories. Moreover, this article demonstrates that a new stage in the cooperation of the Central Asian countries has begun as a result of the initiatives in foreign policy taken by the President of the Republic of Uzbekistan Shavkat Mirziyoyev, which determine the Central Asia a priority direction of Uzbekistan’s foreign policy.